Clocks and robbers - Poblocki, Dan. (New York Scholastic, 2011)
Readers are challenged to unravel the clues along with Viola, Sylvester, Rosie, and Woodrow, who are in pursuit of a treasure hinted at by the Masonic glyphs decorating Moon Hollow's town library.
M
730
M
Keywords: Paranormal fiction; Secret societies -- Juvenile fiction; Supernatural -- Fiction; Secret societies -- Fiction